Sufism, Orthodoxy, and Spirituality: A Critical Reading of Imam Muhammad Abu Zahrah’s Thought - Muhammad Badrun (SUHU: Journal of Sufism and Humanities, 2025)
Objective: This study examines the theoretical foundations of Sufism through the intellectual framework of Imam Muhammad Abu Zahrah, aiming to uncover his interpretive methodology and his position in reconciling Sufi spirituality with Islamic orthodoxy. Method: Employing a qualitative critical-analytical method based on textual analysis of Abu Zahrah’s writings, classical Sufi literature, and secondary theological studies, supported by historical contextualization, the research situates his thought within the broader development of Islamic mysticism and its key figures. Result: The findings reveal that Abu Zahrah adopts a balanced mediating stance: affirming the ethical and spiritual value of Sufism while critiquing speculative excesses and mystical extremism. He advocates for a purified, ethically grounded Sufism aligned with Qur’anic rationality and Islamic creed, thereby distancing it from esoteric deviations. Conclusion: The study concludes that Abu Zahrah’s approach provides a valuable framework for rethinking the role of Sufism in modern Islamic thought, demonstrating its continued relevance for contemporary spiritual renewal and intellectual reform within the Muslim world.